Peningkatan Disiplin Aparatur Sipil Negara Melalui Keterlibatan Apel Pagi - Kusuma, Rhendra; Akadira, Tora; Nurliawati, Nita (Jayapangus Press, 2025)
This study aims to examine the influence of ASN's involvement in morning apples on improving work discipline in government agencies. The morning apple is one of the routine activities held at the beginning of working hours to build discipline, improve communication between employees, and motivate civil servants to start the working day with high enthusiasm. ASN work discipline is one of the important indicators in determining the quality of public services, as well as effectiveness and efficiency in achieving the goals of government organizations. Therefore, the morning apple that is routinely held is expected to create a better culture of work discipline, as well as strengthen the relationship between leaders and subordinates. This study uses a quantitative approach with descriptive design and hypothesis testing to measure the effect of involvement in morning apples on ASN work discipline. The variables studied were the involvement of ASN in the morning apple as an independent variable and work discipline as a dependent variable. Data was collected through questionnaires distributed to civil servants involved in morning apples in several government agencies. Data analysis was carried out using validity and reliability tests, as well as regression analysis to test the relationship between the two variables. The results of the study show that involvement in the morning apple makes a significant contribution to improving the work discipline of civil servants. Involvement in morning apples has been proven to increase the discipline of civil servants in terms of punctuality, compliance with work procedures, and productivity in carrying out duties. In addition, the morning apple also functions as an effective means of communication between management and employees, strengthens relationships between work units, and improves the morale and work spirit of ASN. Leaders who are directly involved in the morning apple set a positive example that strengthens the discipline and responsibility of ASN.